Coeliac Disease and Connection with Iron Deficiency Anemia: A Literature Review - Zielińska, Aleksandra; Szypulski, Szymon; Kowalik, Kinga; Michalska, Maria; Tylczyńska, Kinga; Skiba, Jakub; Iwaniuk, Sebastian; Maciejewski, Ignacy; Tylczyńska, Natalia; Skiba, Zuzanna (Quality in Sport, 2025)
Celiac disease (CD) is one of many autoimmune diseases occurring in children and adults, more often among women, which presents a lot of forms, symptoms. Celiac disease can manifest on the skin, as nutrient deficiencies, or with gastrointestinal symptoms, as well as many other symptoms. One of them is an iron deficiency presented in over half patients with CD related to destroyed absorbing surface - proximal part of small intestine. Many patients with CD present anemia as only one sign. Iron is important microelement in human body essential, among other functions, for oxygen transport in the body and involvement in enzymatic processes and its absorption is regulated by liver protein hepcidin and transport by transferrin in plasma. There are many causes of iron deficiency anemia (IDA), but celiac disease should always be considered as one of them. The immune response to gluten proteins is the underlying mechanism of the disease. The implementation of a gluten-free diet as the primary treatment for celiac disease leads to the improvement and regeneration of the intestinal mucosa, which results in a reduction of the symptoms of the underlying disease, including IDA. Therefore, it is important not to overlook the symptoms of the disease, as its complications can be mitigated.